MULTIFACTORIAL APPROACH TO MORTALITY OF PIGLETS IN SEMI- ARID REGION OF TAMIL NADU - Ramesh, V; Vasantha Kumar, S; Edwin, SC (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
The piglet mortality pattern of Large White Yorkshire pigs were analyzed utilizing the last data available in organized farm. Among the different causes of piglet mortality traumatic shock due to crushing by mother (25.0 per cent), pneumonia (25.0 per cent), hepatitis (17.13 per cent) and haemorrhagic enteritis (13.46 per cent) was found to be common. The percentage of mortality was higher (69.23 pr cent) in 0 to 15 days age group which was mostly due to crushing by mother. As the mortality during the first 15 days was high, it can be concluded that utmost care should be given in early life. Strict hygienic measures will help in reducing the infection related diseases.